Shrinkage influence on stress-strain state of composite masonry members/Susitraukimo deformacijų įtaka kompleksinių mūro elementų įtempių ir deformacijų būviui - Marčiukaitis, Gediminas (Journal of Civil Engineering and Management, 2001)
Composite masonry structures consists of various units (bricks or ceramic, concrete and other blocks) masonry and concrete or reinforced concrete layers. Analysis has shown that in most cases deformation properties of masonry, concrete and reinforced concrete are different. There is a big difference in modulus of elasticity and shrinkage deformations. Methods for determination of shrinkage and modulus of elasticity for different types of masonry and reinforced concrete have been presented. Analysis of distribution of stresses and deformations in layers has shown that for a given difference of shrinkage in layers the stresses of tension and compression in the layers depend on the cross-section area of these layers and the ratio of the modulus of elasticity. Formulas are given for calculation of these stresses.Article in Lithuanian.First Published Online: 30 Jul 2012